ANALISIS PERBEDAAN RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH HOLIDAY EFFECT PADA PERUSAHAAN INDEKS LQ-45 PERIODE 2012-2016 - Martha Ayerza Esra (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
An announcement of a holiday can affect the behavior of investors in trading stocks. The behavior of individual investors in making financial decisions is not only influenced by considerations of economic rationality and objective data, but it is also influenced by irrational actions such as emotions, certain psychological habits, and individual investor mood. Holiday effect is one part of the event study. One or more important holiday in the calendar contains a holiday effect which the stock’s income in the days before the holiday is much higher than weekdays. The method of this research was comparative method. Methods of data collection in this study was observation techniques and the data used were secondary data that obtained from the website dunia investasi. The sampling technique used was purposive sampling technique. The procedures used for testing and data processing were paired samples test using SPSS 22.The results of the research showed that there was a significant difference in stock’s return which average return rate before holiday effect was lower than after the holiday effect. Whereas The research results of trading volume showed there was no difference in trading volume rate either before and after the holiday effect. According to the result of the research, it can be concluded that the holiday effect had an impact on stock returns, however it had no impact on stock trading volume.Keywords : Holiday Effect, Stock Return, Trading Volume Activity, Market Anomalies,Firm Anomalies